Early versus delayed umbilical cord clamping on maternal and neonatal outcomes - Qian, Yiyu (Arch Gynecol Obstet, 2019)
PURPOSE: Policies for timing of cord clamping varied from early cord clamping (ECC) in the first 30 s after birth, to delayed cord clamping (DCC) in more than 30 s after birth or when cord pulsation has ceased. DCC, an inexpensive method allowed physiological placental transfusion. The aim of this article is to review the benefits and the potential harms of early versus delayed cord clamping. METHODS: Narrative overview, synthesizing the findings of the literature retrieved from searches of computerized databases. RESULTS: Delayed cord clamping in term and preterm infants had shown higher hemoglobin levels and iron storage, the improved infants’ and children’s neurodevelopment, the lesser anemia, the higher blood pressure and the fewer transfusions, as well as the lower rates of intraventricular hemorrhage (IVH), chronic lung disease, necrotizing enterocolitis, and late-onset sepsis. DCC was seldom associated with lower Apgar scores, neonatal hypothermia of admission, respiratory distress, and severe jaundice. In addition, DCC was not associated with increased risk of postpartum hemorrhage and maternal blood transfusion whether in cesarean section or vaginal delivery. DCC appeared to have no effect on cord blood gas analysis. However, DCC for more than 60 s reduced drastically the chances of obtaining clinically useful cord blood units (CBUs). CONCLUSION: Delayed cord clamping in term and preterm infants was a simple, safe, and effective delivery procedure, which should be recommended, but the optimal cord clamping time remained controversial.